ISOTOPIC GEOCHEMISTRY OF MESOTHERMAL DEPOSITION OF TALC, TUNGSTEN, AND GOLD: EVIDENCE FROM MINERAL DEPOSITS OF THE URALS - Baksheev I.A.; Kudryavtseva O.E.; Ustinov V.I. (My University, 2004)
Minerals from some talc, tungsten, and gold deposits in the Urals are genetically related to fluids similar in oxygen and hydrogen isotopic compositions. The hydrogen isotopic composition is typical of magmatic fluids. These fluids, responsible for wall-rock alteration and formation of barren propylitic, tungstenbearing gumbeite, and gold-bearing beresite-listwaenite veins at these deposits, had an H2O-CO 2 composition and approximately identical temperatures. Since these fluids are similar in temperature and isotopic composition, the variability of the metasomatites is explained by variations in oxidation potential of the rock-forming environment and the sulfur and potassium regimes. The metasomatites can be arranged in order of decreasing oxidation potential and increasing sulfur fugacity in the following sequence: Propylites, gumbeites, and bereste-listwaenites.